Evaluation of correlation between sagittal balance and plantar pressure distributions in adolescent idiopathic scoliosis: A pilot study. (March 2021) - Yi, Luo; Houwei, Lin; Lin, Wang; Lihua, Zhao; Mengjie, Chen; Sun, Wang; Zejiang, Rao; Qichao, Ma
Abstract: Background: To evaluate the correlation between baropodometric parameters and sagittal parameters for adolescent idiopathic scoliosis. Methods: 44 volunteers (7 males and 37 females) were recruited. All participants were diagnosed as adolescent idiopathic scoliosis by X-ray before baropodometric study. Sagittal parameters included thoracic kyphosis, lumbar lordosis, sagittal vertical axis, pelvic tilt, sacral slope and pelvic incidence. A static baropodometry was performed for each patient. The foot area was divided into four quadrants. The contact surface and weight percentage were measured. Findings: Lumbar lordosis was positively correlated to pelvic incidence, sacral slope and ( P  < 0.001, P  < 0.001, respectively). On the major curve side, pelvic tilt showed a positive correlation with all baropodometric parameters ( P  < 0.05) except forefoot weight percentage. Thoracic kyphosis showed negative correlations with contact surface and weight percentage of the forefoot ( P  = 0.04, 0.02 respectively) but no correlation with any rearfoot feature. Lumbar lordosis, sagittal vertical axis, pelvic incidence and sacral slope were not in correlation with plantar pressure. On the opposite side, sagittal profile showed no obvious correlation with any baropodometric parameter. Interpretation: In scoliosis, sagittal balance is closely correlated to plantar pressure distributions. Baropodometry is a feasible method to assess sagittal balance. Highlights: Sagittal alignment plays a major role in clinical outcomes in adolescent idiopathic scoliosis. The distributions of the plantar pressure indicate important postural abnormalities. The relationship between sagittal balance and plantar pressure has been studied. Sagittal balance is closely correlated to plantar pressure distributions. Baropodometry is a feasible method to assess sagittal balance.